(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Abstract- The prevailing challenges in contemporary research paper publication, including centralization, limited access, prolonged distribution, high publication costs, lack of transparency, slow publication timelines, limited visibility for lesser-known researchers, copyright and ownership issues, inefficient peer review processes, and language barriers, prompt a transformative solution. This research proposes a modern system leveraging blockchain and smart contracts to revolutionize the traditional publication model. Employing Ethereum smart contracts, the proposed system expedites publication, mitigates bias in evaluations, and reduces costs. Innovative features enhance study quality, while the decentralized model ensures traceability and global accessibility for scientific papers with a nominal fee. The proposed system integrates tokenization to establish explicit author ownership and decentralized control, fostering efficient peer review through a token-based incentive structure. This inventive strategy aims to redefine research paper publication, promoting transparency, accessibility, and efficiency. The transformative system has the potential to reshape scholarly communication, unlocking new possibilities for the global propagation of research knowledge.